IMPLEMENTASI METODE PROMETHEE PADA SISTEM PENDUKUNG KEPUTUSAN DALAM MEMBERIKAN REWARD TERHADAP CUSTOMER PADA APLIKASI BENGKEL - fina fatathul khasanah; Cecep Juliansyah Abbas; Dadan Nugraha (Sistem Informasi Fakultas Ilmu Komputer Universitas Kuningan, 2019)
In the world of business, competition has become a thing that has been already familiar, the number of businesses with the same type make an entrepreneur to have a strategy in increasing customer purchasing power. One strategy that can be applied is to give rewards to customers. Honda Prima Motor Kuningan AHASS Workshop 00773 has problems in giving awards or rewards to customers, the system used today has not integrated with the data processing process, the Honda Prima Motor workshop feels that the current system is still not effective and efficient. In order to make the transaction process and assist customers who are entitled to get Reward recorded efficiently and effectively, a Decision Support System is needed to manage customer transaction data and it can facilitate the workshop in determining customers who are entitled to get a Prize from the Honda Prima Motor workshop. This Decision Support System is built using the Promethee method, where the Promethe method is one of the methods for determining priority order in MCDM (Multi Criterion Decision Making). The use of the Promethee method is to determine and produce decisions from several alternatives. This system is built using the PHP programming language and uses a MySQL as database and it can produce a system that can help the prime Honda Prima Motor determining customers who are entitled to a reward.